Vocabulary Learning Strategies Vis-a- Vis Vocabulary Teaching Strategies - Abrar Kedir Mohammed (Journal of Languages and Language Teaching, 2023)
Learning a foreign language entails a learner to develop special effort or ways of learning to acquire the target language effectively. This can be achieved through using appropriate learning strategies. Thus, this article looks at the relationship between vocabulary teaching methods and vocabulary learning strategies employed by students and teachers in secondary schools. Mixed methods design was used to collect quantitative and qualitative data. Data were collected through questionnaire, interview and classroom observations. Separate analyses of the data were conducted, and the qualitative findings were used to support the numeric findings. The results showed that because teachers weren't always using them to teach vocabulary lessons, vocabulary teaching strategies were found to be less effective and practical in the sample schools. It also found that the students were unable to effectively use techniques for learning new word meanings and cementing them in their long-term memory. As a result, vocabulary teaching and learning methods have not received much attention from teachers and students.  Thus, teachers should be given refreshment trainings on the teaching strategies of vocabulary so as to help students to make use of vocabulary learning strategies. Besides, it is suggested students’ training on how to use the strategies and promote the sense of autonomous learning..